Effects of Accounting Information System on Organizational Profitability in Nepalese Commercial Banks - Yadav, Bimlesh Prasad (Nepalese Journal of Business, 2024)
This study examines the effects of accounting information system on organization profitability in Nepalese commercial banks. Return on assets (ROA) and return on equity (ROE) are the selected dependent variables. The selected independent variables are non performing loan (NPL), loan loss provision (LLP), capital adequacy ratio (CAR), credit to deposit rate (CRR) and bank size (BS). The study is based on secondary data of 15 commercial banks with 120 observations for the study period from 2014/15 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of effects of accounting information system on organizational profitability in Nepalese commercial banks. The study shows that non-performing loan has a negative impact on return on assets and return on equity. It indicates that increase in non-performing loan leads to decrease in return on assets and return on equity. Similarly, credit to deposit ratio has a negative impact on return on assets and return on equity. It indicates that increase in credit to deposit ratio leads to decrease in return on assets and return on equity. Likewise, loan loss provision has a negative impact on return on assets and return on equity. It indicates that increase in loan loss provision leads to decrease in return on assets and return on equity. However, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to increase in return on assets and return on equity. Further, bank size has a negative impact on return on assets and return on equity. It indicates that increase in bank size leads to decrease in return on assets and return on equity.